Reorganising the lobster fishery value chain. (October 2020) - Botha, Mark
Abstract: In South Africa, approximately 38% of the net revenue attained from the near-shore lobster fishery value chain accrues to small-scale fishers. The remainder accrues to industrial processors and export marketeers. Moreover, the median annual net income attained by a typical small-scale fisher is less than a State Welfare grant recipient, which is problematic. This study examines the impact of reorganising the value chain for the high value West Coast rock lobster species— Jasus lalandii —on the economic welfare of fishers. The 2016–17 fishing season in the Northern and Western Cape provinces is examined through a mixed research method and various scenarios are presented. The measures presented in the scenarios of value chain reorganisation ought to improve the economic welfare of fishers by at least 136%. The potential for growth is even more profound with the introduction of market timing. This study provides insight into a coordinated developmental approach to improve the livelihoods of coastal community fishers.